The interpretation of the will - Vidal Ramírez, Fernando (2007)
The testamentary act is the manifestation of will of the testator by which he arranges his assets in a total o partial way for after his death. Therefore, the interpretation of this act is a resource to establish the sense to the will of the testator, resorting to the general rules of interpretation of the second book of the Civil Code dedicated to the juridical activity, which are developed by the author in the following lines.